Old Inns in Southwark : Dog and Bear and Old Croyden House, King's Head, Catherine Wheel, Queen's Head, The George. (Tufts Archival Research Center, 2006)
This illustration is from Edward Walford "Old and new London, a narrative of its history, its people, and its places, vol. 6"